Gold Nanoparticles to Tackle Drug Resistance in Cancer - Pedrosa, Pedro Miguel Pinto Gonçalves Gouveia (2019)
The most common type of cancer treatment, chemotherapy, often fails due to the acquisition of resistance. It is therefore of the utmost importance to better understand the cellular mechanisms of resistance, while developing new strategies to tackle drug resistance. Nanomedicine promises to develop new tools for diagnosing and treating of diseases, improving human health. This thesis explored five main strategies to overcome drug resistance in cancer cells: i) new anti-cancer compounds, ii) nanovectorisation and targeting of compounds, iii) gold nanoparticles (AuNP) for hyperthermia and combination with chemotherapy iv) AuNP assisted angiogenesis arrest with laser ablation and chemotherapy v) AuNP mediated gene silencing of efflux pumps. We started by characterizing the mechanism of action of a new anti-tumour compound (ZnD), that was able to reduce the viability of a colon cancer cell line (HCT116 DR) resistant to doxorubicin (DOX), a first-line chemotherapeutic. We vectorized our compound with AuNP, resulting in increased toxicity to HCT116 DR mouse xenografts. Taking advantage of the photothermal properties of AuNP, we combined chemotherapy with photo hyperthermia by irradiating AuNP with a green laser. Hyperthermia was especially effective against HCT116 DR. Since angiogenesis is a milestone in cancer development, we aimed to prevent it, using an anti-angiogenic peptide vectorized with AuNP and laser irradiation, resulting in a vascularization reduction of 91% in vivo. We have observed that ABCB1 efflux pump was the major cause of resistance of DOX resist cell line, therefore we silenced its mRNA with an anti-sense oligonucleotide AuNP. Our results showed that although the silencing was effective, cells did not return to a sensitive phenotype, requiring further experiments. Altogether this thesis shows the potential of nanotechnology for cancer treatment, both in chemotherapy and in surgery, where green lasers are already used. This work can be applied to drug resistant tumours, increasing the efficacy of treatment.